Post Radiotherapy Uro-gynaecological Morbidities in Cancer Cervix-Retrospective Study (KYAMC Journal, 2013)
Aims & Objectives: This study aimed to investigate the complications related to uro-genital system of patients who received radiotherapy for invasive cervical cancer. The patient selection is randomized who were evaluated in OPD Obst. Gynae. Deptt.of KYAMCH after receiving their full course of radiotherapy.100 patients were evaluated. In this study most of the women were perimenopausal, having 2-5 children, most of them were presented with vaginal discharge & postcoital bleeding, most of them received surgical treatment followed by radiotherapy & chemotherapy. During radiotherapy most of them having no complains, some of them were suffering from frequency of micturation & dysuria. 31% patient suffered from dyspareunia, 17% vaginal stenosis, 7% vaginal discharge and 7% cystitis. KYAMC Journal Vol. 3, No.-2, January 2013, Page 273-276 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15166